Incidence of Type 2 Diabetes by Place of Birth in the Multi-Ethnic Study of Atherosclerosis (MESA) - Oza-Frank, Reena (2013)
Incidence of diabetes among US foreign-born individuals is not well studied. Data were from the Multi Ethnic Study of Atherosclerosis. Cox proportional hazards regression was used to examine diabetes risk by race/ethnicity, place of birth, and duration of residence among foreign-born. Foreign-born Latinos had a higher risk of incident diabetes compared to US-born Latinos (hazard ratio (HR) 1.79 [95 % confidence interval (CI) 1.00–3.21]). Latinos born in Mexico (HR, 2.26 [95 % CI, 1.18–4.33]) had higher risk of incident diabetes compared to US-born Latinos. Foreign-born living in the US ≥20 years had a higher adjusted risk of incident diabetes compared to those in the US for <20 years (HR, 1.60 [95 % CI, 1.05–2.55]). Incident diabetes may be higher among foreign-born compared to native born; incident diabetes may also be higher among those immigrants who have lived in the US for longer periods of time. Future studies should characterize individuals by race/ethnicity and place of birth to account for differences in biology and time spent in the US.